Penerapan Konstitusi Sebagai Objek Kajian Hukum Tata Negara di Indonesia - Muhamad Habibullah AR; Nopan Harnata; Windy Adiska Irani (STAI Bumi Silampari, 2025)
A constitution is a set of rules within a state and plays a vital role within a country. This journal attempts to examine the importance of a constitution for each country. This research method uses a qualitative approach aimed at organizing and sorting data into patterns, categories, and basic descriptive units so that themes can be found and working hypotheses can be formulated as suggested by the data. In an effort to find a good constitutional rule, interpretative efforts are needed, the constitution as a result of an assessment of the implementation of norms in a constitution in practice. The constitution in Indonesia has a complex history and has gone through a long debate. Where Indonesia itself had to go through four amendments, including in 1999, 2000, 2001, and 2002. Indonesia is one of the countries that uses a written constitution, namely the 1945 Constitution of the Republic of Indonesia (UUD 1945). The desired goal is to see the implementation of the existing constitution in Indonesia and the future challenges that we must anticipate together for all Indonesian people. In this study, the method used is qualitative research with a library approach. The findings of this study indicate that the application of the Constitution in the study of constitutional law has been successful. We acknowledge that there are still shortcomings that require our collective attention, and future challenges that require our collective attention and concern as a society with increasingly growing multiculturalism and transnationalism.